FAKTA DAN SEJARAH Usaha Mengkaji Alam Pikiran di Balik Peristiwa Historis - A. Eddy Kristiyanto (Studia Philosophica et Theologica, 2016)
There is an expression in learning history like this: “Nothing is new in history, except the way of reading and new hermeneutics over historical events.” Such an expression is not thoroughly false, since human experience makes new understanding or even sometime makes new discovery of historical facts. History is not changeable on the one hand, but interpretation and hermeneutics over history is always developing on the other. Historical perspective is also in its part changing “history”. Historian being in disposal to serve humanity should be open and faithful to the objective truth of history that is based on various sources of historical data. Wieesteingentlichgewesendoes not stand alone without foundation of ideas, interests pursued, and even psychological motivation. Rereading of the past events and our understanding of them are but spirit or soul of historical study. Research, choice, formulation, and publication of historical sources become sort of scientific dialogue-field in the midst of amnesia and instant culture. In this article, we deal with how historian emerges himself into his scientific field in order to pursue quality of contribution to humanity. One of topics dealt with is about the past event that, we believe, is a formative treasure of humanity. The characteristic of that treasure is socialcultural. We do believe that unless with freedom from serving to political power, we can not put forward good contribution to the quality of living together with dignity simply because historical study goes along with concrete culture of people